Factors that influence breastfeeding initiation and duration in urban, suburban and rural areas of Zhejiang Province, Peoples Republic of China - Qiu, Liqian (Curtin University, 2008)
Introduction: Breast milk is the best way to feed all infants. It results in better nutrition for the infant and to reduced rates of chronic disease later in childhood and adulthood. Breastfed babies have lower rates of infectious diseases and will not be exposed to contaminated infant formula, such as the recent experience with melamine in China. The WHO Expert Consultation on Infant Feeding recommended exclusive breastfeeding for six months, with the introduction of complementary foods and continued breastfeeding thereafter. It was also recommended by the WHO that breastfeeding continue beyond six months for up to two years and beyond. Breastmilk can provide the majority of nutrients for the first 12 months of life. Complementary foods were given in the second half year gradually.However with the rapid economic development, the traditional home based obstetric system in China has changed. Following the change in women’s living styles, traditional infant feeding perceptions and practices have changed. Women now have high rates of returning to work after delivering a baby, especially in the urban areas, and more infants are being given infant formula and other substitutes for breastfeeding. Zhejiang Province is the one of fastest developing economic regions located in the mid Eastern coast of China. The breastfeeding rate has dropped rapidly since the 1970’s. This has significant implications for the child health in this region. A longitudinal study of breastfeeding was needed to provide the data necessary to implement a comprehensive health promotion program. Efforts are needed to promote breastfeeding, which should be one of the highest health promotion priorities.The aim of this study was to document the prevalence and duration of breastfeeding and exclusive breastfeeding in city, suburban and rural areas in Zhejiang Province; analyze the factors determining the initiation and the duration of breastfeeding; document mothers’ knowledge about the benefits of breastfeeding; identify the prevalence of problems associated with breastfeeding and constraints to exclusive breastfeeding up to six months of life; document the prevalence of prelacteal feeds and finally to describe differences in breastfeeding between city, suburb and rural area.Method: In order to achieve these objectives a longitudinal cohort study was undertaken of infant feeding practices in three locations in Zhejiang Province which represent city and suburban and rural areas. Mothers who delivered babies during 2004 and 2005 were randomly selected from the obstetric wards while in hospital and invited to voluntarily participate in the study. The mothers were interviewed in hospital and after discharge, were contacted by telephone three more times at 1, 3 and 6 months. The few mothers who could not be reached by telephone were interviewed during the scheduled routine immunisation clinics at their local MCH clinic. On each of these follow up occasions they were interviewed using a structured questionnaire to obtain details of infant feeding practices. A total of 1520 mothers were recruited in 4 hospitals located in city, suburb and rural areas. Almost all mothers (98%) agreed to participate. All data analyses were carried out using the Statistical Package for Social Science (SPSS), release 14.0 (SPSS Inc., Chicago, IL, USA). Descriptive techniques and survival analysis were used to document breastfeeding rates and duration. Cox regression analysis was undertaken to explore factors affecting breastfeeding.Results: Of the total 1520 mothers were recruited into the study, 628 were from the city, 347 from the suburb and 535 from the rural area. Breastfeeding initiation rates were high in all three locations. Initially more than 95% of the mothers began breastfeeding, but only 50.3% babies averagely in three locations were being exclusively breastfed at discharge. The number of infants being exclusively breastfed prior to discharge was relatively low. Exclusive breastfeeding before discharge was positively related to delivery method, the first feed given to the baby, mother’s place of residence, mother’s age, mothers’ education level and family income.‘Any breastfeeding’ rates at discharge and at 1, 3 and 6 months were 96.9%, 96.0%, 89.7% and 76.7% respectively. ‘Exclusive breastfeeding’ rates at discharge, and at 1, 3, 6 months were 50.3%, 55.1%, 45.8% and 3.9% respectively. The average duration of ‘exclusive breastfeeding’ was 44.7 days (95% CI, 41.6-47.9).Overall about half of mothers gave the babies prelacteal feeds before commencing breastfeeding. This situation was more common in city, compared with the suburban and rural mothers. The prelacteal feeding rates were 62.0%, 36.6% and 39.0% in city, suburb and rural area respectively.The breastfeeding rates differed by location between the city, suburb and rural areas. ‘Any breastfeeding’ rates in the city, suburb and rural area at discharge were 96.5 %, 96.8 % and 97.4 % respectively, the ‘exclusive breastfeeding’ rates in city, suburb and rural area at discharge were 38.0%, 63.4 % and 61.0 % respectively. The rates of exclusive breastfeeding at six months were only 0.2%, 0.5 % and 7.2 % respectively, well below the Chinese and WHO targets.The risk factors related to cessation of ‘any breastfeeding’ were ‘mother’s age’, ‘the time the decision to breastfeed was made’, ‘whether the infant was admitted to special care nursery’, ‘mother’s return to work within 6 months’, ‘the early feeding of water and /or other complementary foods, and location of mother’s usual residence. Factors negatively associated with ‘exclusive breastfeeding’ duration were early return to work and to place of residence, with the mothers living in the rural area exclusively breastfeeding for longer.Delivery method was an important influence on breastfeeding. In this study the highest caesarean section rate was in the city (76%), with a similar rate in the suburbs (74%) and the lowest in the rural area (53%). Mothers who had a caesarean section were less likely to be exclusively breastfeeding on discharge (35.8% in city, 59.6% in the suburbs) compared to vaginal delivery where the rates were 45% and 74.4% respectively. The adjusted odds ratio for exclusive breastfeeding in caesarean section deliveries in the city and suburban mothers was 0.64 (95% CI 0.46, 0.88).Conclusion: The study has descried the initiation and duration of breastfeeding (to six months) of babies in the different areas of Zhejiang Province. Separate information is provided on the prevalence of ‘any breastfeeding’ and ‘exclusive breastfeeding'. The factors that are associated with the initiation and duration of breastfeeding in Zhejiang Province are documented. Health promotion programs are needed to change some traditional inappropriate breastfeeding perceptions and to promote ‘exclusive breastfeeding’ in the first six months of life in Zhejiang. Education should be given and regulations should be introduced restricting hospital staff from recommending prelacteal and supplementary feeds unless warranted for medical reasons. The research also shows that there would be a benefit to breastfeeding if delivery and lactation leave were extended to six months and if the incidence of caesarean section could be reduced to levels more consistent with WHO expected levels.